Otimização da extração e caracterização parcial de celulases fúngicas obtidas por fermentação em estado sólido do bagaço da cana-de-açúcar - Alves, Tales Prado (2017)
Brazil is the world's largest producer of sugarcane, this product is mostly destined for the production of sugar and fuel alcohol, giving rise to a large volume of solid waste. Sugarcane bagasse is a lignocellulosic residue that has been used mainly in energy generation. In the search for more noble purposes, sugarcane bagasse can be used in solid state fermentation processes (FES), intended for the production of enzymes capable of hydrolyzing cellulose. The extraction of the enzymes obtained in FES with fungi is an important step that can influence the yield and cost during the process of obtaining the enzymatic extracts, which will be used in the hydrolysis processes of the cellulose present in sugarcane bagasse, for the purpose of production fermentable sugars, which will serve as raw material in subsequent fermentations to obtain bioethanol. The objective of this work was to evaluate the best conditions for the extraction of cellulase enzymes (FPases, CMCases and β-glycosidase) obtained by FES from sugarcane bagasse with the Aspergillus niger fungus and its partial characterization. The optimization of the extraction process of the cellulolytic enzymes by experimental designs in search of the optimal condition for multienzymatic extraction was investigated, using ultrasound (Ultra) and temperature (°C) and time (min) and pH involved in the process. The results obtained from the Doehlert Matrix showed that there is no significant influence (p <0.05) on the use of Ultra in the enzymatic complex extraction. Based on the Box-Behnken design, taking as variables t, T and pH, the statistical analysis showed significant effects of quadratic terms (Q) T, t and pH for FPase. For the CMCase the terms t (Q), linear of the T (L) and the interaction of the terms T (L) and pH (L) were significant, for β-glycosidase the term of T (Q) and pH (L). The obtained models describe in a satisfactory way the process of extraction of the enzymes, affirmed by the values of R2 and test F. The optimization of the extraction was estimated with global desirability of 0.80, under the operating conditions: t = 35.8 min, T = 38.3 °C and pH = 6.5. In hydrolysis of sugarcane bagasse using the enzymatic complex, the ANOVA and the Tukey test demonstrated that the best treatment was the ultrasonic assisted hydrolysis, with a mean value of 0.818 g L-1 in the highest solid-liquid ratio of 33, 3 g L-1 studied. Partial characterization of cellulase in temperature and pH showed that cellulase is thermostable at temperatures of 50°C and 60°C and stability at pH in the range of 5 to 7.